Policy Evaluation Implementation of Risk-Based Business Licensing in Kuningan District - Agus Susanto; Diah Nurjanah; Yanto Sugianto; Yanto Suharyanto; Ipik Permana; Nursahidin Nursahidin (CV. Syntax Corporation Indonesia, 2024)
The policy performance of implementing Risk-Based Business Licensing through the Online Single Submission-Risk Based Approach (OSS-RBA) system in Kuningan Regency is still experiencing obstacles because Kuningan Regency does not yet have a Detailed Spatial Plan (RDTR) which has an impact on hampering the process of basic requirements in the form of Conformity of Space Utilization Activities (KKPR), Environmental Approval and Building Construction Approval (PBG). Therefore, it is necessary to evaluate the business licensing policy so that the aim of the policy, namely improving the investment ecosystem through issuing business permits more effectively and simply, can be achieved. This research uses qualitative methods with data collection and analysis techniques through observation, interviews with service officers and the community as well as documentation studies. Based on the results of research using William N Dunn's evaluation theory with 6 main criteria, it was concluded that the implementation of risk-based business licensing policies in Kuningan Regency has not met effectiveness, efficiency, adequacy, alignment and accuracy in encouraging ease of business licensing even though the responsiveness is quite good with the increasing number of permits. Micro and Small Enterprises (IUMK) in Kuningan Regency. To increase the effectiveness of implementing this policy, the Kuningan Regency government issued a regional policy so that the business licensing public service process in Kuningan Regency continues to run well.